Accelerated GWT Building Enterprise Google Web Toolkit Applications - Gupta, Vipul (Apress : Imprint: Apress, 2008)
Ajax is a web development technique that takes advantage of JavaScript to display and interact dynamically with information embedded into a web page. Its emergence has made it possible to create web applications that closely resemble their desktop-based brethren. With this exciting new ability came several challenges; not only did developers have to learn JavaScript, but they were also forced to use inefficient development processes, not to mention deal with cross-platform and browser difficulties. But with the release of Google Web Toolkit (GWT), Java developers are able to continue using their favorite language to write powerful Ajax applications while using not only the Java language, but also the very same development tools they're already using on a daily basis! Serious Java developers wanting to write Ajax applications using GWT can expect a fast-paced, yet thorough, introduction to GWT from Java expert Vipul Gupta. You'll gain key insights into the GWT framework's capabilities and can rely on clear instruction that will show you how to incorporate GWT into your daily development routine in the most effective way. Accelerated GWT introduces you to the popular GWT framework in a way that will allow you to begin using GWT in short order. Forgoing superfluous introductions to JavaScript and Ajax, you'll instead be immersed in GWT fundamentals from the very first chapter. Subsequent chapters discuss key GWT concepts such as architecture, widgets, and RPC. Understanding you'll want to efficiently integrate GWT into your development workflow, the author also devotes time to sound GWT application design, testing, and internationalization issues.